Isolation of Protective Somatic Antigen from Vibrio cholerae (Ogawa) Ribosomal Preparations - Jensen, Ronald (1972)
Ribosomal preparations from Vibrio cholerae Ogawa and Inaba are protective immunogens for mice challenged with either serotype. Column chromatography of ribosomal fractions separated protective antigen from the ribosomes. The antigen is a heterogeneous colloid which contains protein, lipid, and carbohydrate in the ratio 3:1:1. Amino acid composition is that of a slightly acidic protein with no unusual complement of amino acids. The lipid component consists of several longchain fatty acids and of phosphatidyl ethanolamine. The major sugars identified were glucose and galactose. The colloid can be dissolved by treatment with chelating agents and sodium dodecyl sulfate. Purification of the solubilized material or of the colloid was unsuccessful.